(untitled) - Kirn, Elaine (Thành phố Hồ Chí Minh ; New York, 2009)
Language proficiencies are articulated across five ability levels (beginning through advanced) within each of the four language skill strands. Chapter themes articulate across the four skill strands to systematically recycle content, vocabulary, and grammar. This is the low intermediate to intermediate level Grammar student book.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Grammar,Textbooks for foreign speakers,Ngữ pháp,Sách dùng cho người nước ngoài